Porous polymer membrane

CN123022484APending Publication Date: 2026-10-30SARTORIUS STEDIM BIOTECH GMBH
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202580023874.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-28
Filing Date
2025-03-25
Publication Date
2026-10-30

Smart Images

  • Figure CN123022484A_ABST
    Figure CN123022484A_ABST
Patent Text Reader

Abstract

The present invention relates to a porous polymer membrane having a specific average pore size, a specific thickness and a specific combination of convective porosity. Furthermore, the present invention relates to a method of manufacturing such a porous polymer membrane.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This invention relates to porous polymer membranes having a specific combination of average pore size, specific thickness, and specific convective porosity. Furthermore, this invention relates to a method for manufacturing such porous polymer membranes.

[0002] Membranes, or adsorption membranes, serve as selective barriers for separating two phases. To achieve their selective purpose, membranes must provide pores that allow passage from one side to the other. Specifically, such membranes can possess various functions, such as size exclusion of specific substances, non-specific binding of hydrophobic substances, or specific binding of substances carrying corresponding reactive groups.

[0003] Specifically, with the aid of adsorbent materials, membranes can be used for membrane chromatography or for the chromatographic separation and purification of fluids. In the case of adsorption, the adsorbent is a porous solid that can selectively form bonds with certain components of the fluid through functional surface groups, referred to as ligands or chromatographic active centers. The target substance and / or pollutant can be a monomolecule, an adsorbate, or a particle, which can be, for example, a protein or other biologically derived substance. The adsorbent can simultaneously carry two or more types of functional groups on its inner and outer surfaces. The binding of the adsorbate to the adsorbent can be reversible or irreversible.

[0004] In bind-elution chromatography, a fluid / mobile phase flows through or across a stationary chromatographic phase. A portion of the components in the mobile phase are bound, and the remaining components are filtered out or passed through. Thus, specific components are bound to the stationary phase and can subsequently be eluted to obtain the purified form of the component.

[0005] Typically, the porous structure of a membrane depends on the manufacturing method in which a solid polymer surrounds the pores of the membrane. Such membranes can be prepared using various methods, such as combining phase separation and solvent evaporation. That is, the pore structure is generated by a separation process in which a liquid polymer solution is applied as a thin layer onto a support, and in a subsequent evaporation step, the solvent (mixture) of the polymer is removed. Due to evaporation, the polymer becomes insoluble in the resulting solvent-reduced mixture, leading to the separation of a polymer-rich phase and a polymer-reduced phase. During continued evaporation, the polymer-rich phase solidifies, while the polymer-reduced phase disappears due to evaporation, resulting in a porous membrane. Typically, this process depends on various parameters, such as the evaporation rate, temperature, and the initial polymer concentration of the polymer solution.

[0006] Because the polymer layer is applied to the carrier, evaporation occurs only on the exposed surface of the polymer layer, during which the temperature and composition of the layer surface continuously change. Therefore, in the aforementioned production method, the main challenge for achieving a symmetrical membrane is to adjust the production process in a way that ensures sufficient evaporation time so that the polymer layer can adapt to changes in temperature and composition through diffusion. This challenge is particularly difficult to overcome for symmetrical membranes with high thickness.

[0007] Membranes used for binding and elution chromatography should meet several requirements depending on the specific application. Generally, such membranes should have high binding capacity while maintaining a high flow rate of fluid passing through or across the membrane. Binding capacity is particularly related to the inner surface of the membrane, which is accessible to the components of the fluid, and this inner surface is related to the membrane's porosity. Furthermore, the physical requirements of the application of such membranes, such as thickness and pressure resistance, should also be considered.

[0008] In other words, high binding capacity is primarily improved through membrane thickness and a high internal surface area, which in turn depends on the membrane's convective porosity. On the other hand, high flow rates are achieved by providing membranes with large average pore sizes. Furthermore, membrane permeability is related to a specific internal surface area in such a way that only one of these parameters can be optimized simultaneously: increasing the specific internal surface area of ​​the membrane leads to decreased permeability (i.e., lower flow rates and yields in chromatographic applications), while neglecting to increase permeability leads to decreased specific internal surface area (i.e., lower binding capacity).

[0009] However, membranes known in the prior art, depending on the specific application, only possess achievable large thicknesses, high convective porosity, or large average pore sizes. Due to technological challenges, the production of membranes achieving a combination of these requirements has not yet been realized. Furthermore, as mentioned above, permeability and specific internal surface areas cannot be optimized independently.

[0010] Therefore, in view of the above, the technical problem to be solved by the present invention is to provide a membrane that can be used as a chromatographic material, the membrane having a high binding capacity while maintaining a high flow rate of fluid flowing through or through the membrane.

[0011] The solution to the above-mentioned technical problem is provided by the embodiments described in the claims.

[0012] Therefore, the present invention provides a porous polymer membrane having a first main surface, a second main surface, and membrane bridges, wherein the membrane bridges are solid polymer bulk materials surrounding and defining the pores of the membrane. The polymer therein is a polysaccharide.

[0013] The average pore size of the membrane pores in the porous polymer membrane is between 0.45 µm and 10.0 µm.

[0014] The porous polymer membrane has a thickness of 150 µm to 1000 µm, and

[0015] The convective porosity of the porous polymer membrane is at least 65%, and

[0016] The porous polymer membrane exhibits a relationship between permeability (P) and a specific internal surface area (Ai) as defined by the following equation (1):

[0017] Where P is the permeability in mD, and A i For m 2 The specific internal surface area relative to the weight of the porous polymer membrane, in units of g, is A at least 835 mD, B at least 1.10 g / m², and C at least 14 mD.

[0018] The polymer of the porous polymer membrane is a polysaccharide. In this document, the term polysaccharide refers to polymerized compounds in which monosaccharide units are linked together by glycosidic bonds.

[0019] The porous polymer membrane of the present invention (hereinafter sometimes simply referred to as "polymer membrane") has a first main surface, a second main surface, and membrane bridges, wherein the membrane bridges are solid polymer bulk materials surrounding and defining the pores of the membrane. That is, the membrane described herein comprises at least two phases: a solid polymer bulk phase forming the membrane bridges, and at least one second phase between the membrane bridges forming the pores.

[0020] In the porous polymer membrane of the present invention, the average pore size is 0.45 to 10.0 µm, preferably 0.60 to 8.0 µm, more preferably 0.80 to 6.0 µm, even more preferably 1.0 to 5.0 µm, and most preferably 1.5 to 4.0 µm. In this document, the average pore size is determined using confocal laser scanning microscopy (CLSM). Specifically, the CLSM is performed as described, for example, by Ley, A. et al. in Journal of Membrane Science 564, 2018, 543-551 (page 545). In this document, the term "average" is used in relation to the average pore size.

[0021] Furthermore, the porous polymer membrane of the present invention has a thickness of 150 to 1000 µm. As used herein, the term "thickness" refers to the shortest distance perpendicular to the two surfaces from the first primary surface to the second primary surface of the membrane. Preferably, the thickness is 200 to 750 µm or 200 to 500 µm, more preferably 220 to 500 µm or 220 to 350 µm, and most preferably 250 to 450 µm or 250 to 330 µm. Compared to thin polymer membranes, this thickness achieves high mechanical stability and high binding capacity per membrane.

[0022] Furthermore, the convective porosity of the membrane is at least 65%. In this document, convective porosity is defined as the volume of the convective pores (V). 对流孔 Divide by the total volume of the intact membrane (V) 完整的膜 The total volume of the complete membrane is V. 对流孔 and the volume (V) of the polymer membrane material 聚合物膜材料 The total volume of the polymer membrane material includes an optional support (described below). In this document, the volume of the convection pores of the membrane can be determined by reversed-phase size exclusion chromatography, well known to those skilled in the art, and is exemplarily shown in a modified form in Journal of Chromatography A - J CHROMATOGR A. 731. 27-40. 10.1016 / 0021-9673(95)01197-8; or in the case of neutral or negatively charged membranes, by the dextran blue method according to, for example, Example 14 on pages 39-42 of WO 2009 / 127285 A1, and the volume of the complete membrane can be determined, depending on the shape of the membrane, such as a cylinder, by measuring the geometric thickness and dimensions and calculating the volume.

[0023]

[0024] in,

[0025] The “polymer membrane material” used above is a polysaccharide polymer material and (optionally) a support, and therefore the volume of the polymer membrane material is the sum of the volumes of the polysaccharide polymer material and (optionally) the support.

[0026] In a preferred embodiment, the convective porosity is 70%, more preferably 75%, even more preferably 80%, and most preferably at least 85%. Furthermore, the convective porosity is at most 90%. If the convective porosity is at least 65%, an excellent balance is achieved between the flow rate of the solution through the membrane and the high internal surface area. By providing a convective porosity of at most 90%, the stability of the membrane can be ensured, as the stability of the membrane may deteriorate at very high convective porosities.

[0027] Furthermore, the porous polymer membrane exhibits a relationship between permeability (P) and a specific internal surface area (Ai) as defined by the following equation (1):

[0028] Where P is the permeability in mD, and A i For m 2 The specific internal surface area relative to the weight of the porous polymer membrane, expressed as / g. Additionally, A is at least 835 mD, preferably at least 935 mD, more preferably at least 985 mD, and most preferably at least 1035 mD. B is at least 1.10 g / m², preferably at least 1.20 g / m². 2 More preferably at least 1.25 g / m 2 And the optimal value is at least 1.30 g / m 2 C is at least 14 mD, preferably at least 16 mD, more preferably at least 18 mD, and most preferably at least 19 mD. The parameters A, B, and C are empirical parameters. To determine whether the membrane satisfies equation (1), the minimum values ​​of A, B, and C are selected, and the permeability and a specific internal surface area are measured. Since equation (1) represents an inequality, the minimum values ​​of A, B, and C as described above are used to derive equation (1) describing the maximum range of permeability and a specific internal surface area.

[0029] Although P(A) i There is no particular upper limit to the permeability (P), but the porous polymer membrane can exhibit the permeability (P) defined by the following relationship (2) with a specific internal surface area (A). i The relationship between )

[0030] Permeability can be determined by the following formula, as described by Ley et al., Journal of Membrane Science 564, 2018, 543-551 (page 545):

[0031] Where P represents permeability, ν represents area-dependent flow rate, µ represents water viscosity, Δx represents the thickness of the layer through which the fluid flows, and Δp represents the pressure difference (see Darcy's Law). In this paper, the thickness of the layer through which the fluid flows can be determined using a conventional thickness gauge, such as the J50C (Käfer, Germany). The permeability was determined as follows: using a 47mm die-cut membrane mounted in a housing equipped with a water tank, a pressure of 100 mbar was applied, and the time required for 100 mL of water to pass through the membrane at ambient temperature (i.e., 18 to 23 °C) was measured. In this paper, the membrane measured was a porous polymer membrane including optional supports (described later).

[0032] Porous polymer membranes possess a high internal surface area, and therefore a high binding capacity for analytes. In this document, the internal surface area is determined by a BET method known to those skilled in the art, and described in, for example, at Atkins, “Physikalische Chemie”, 3rd edition, pp. 934-936, using a Micromeritics Gemini VII and nitrogen as the measuring gas. The determined value can be specified as m normalized to the corresponding weight or volume of the sample. 2 / g or m 2 The unit is / mL. According to a preferred embodiment, the specific internal surface area of ​​the porous polymer membrane is 0.5 to 12 m². 2 / g, more preferably 1.0 to 10.5 m 2 / g, and the most preferred value is 1.5 to 8.0 m 2 / g.

[0033] Due to the specific combination of average pore size, thickness and convective porosity, and the fulfillment of the relationship between permeability and a specific internal surface area (1), it is advantageous to provide membranes that achieve high binding capacity while maintaining high flow rates in chromatography.

[0034] In a specific embodiment, the porous polymer membrane of the present invention is a phase inversion membrane. Hereinafter, the term "phase inversion membrane" refers to a membrane formed during a layering process under conditions inducing the polymer to become insoluble through, for example, changes in concentration, temperature, or solvent environment. Evaporation or precipitation casting are typical methods for achieving this.

[0035] Preferably, the porous polymer membrane has a permeability of 20 to 5000 mD, more preferably 30 to 500 mD, even more preferably 50 to 350 mD, even more preferably 55 to 300 mD, still more preferably 60 to 250 mD, even more preferably 75 to 230 mD, and most preferably 100 to 200 mD. If the permeability of the membrane is within the above-mentioned range, the membrane is characterized by a good balance between the analyte flow rate and the binding capacity. This balance is particularly excellent within the above-mentioned preferred range.

[0036] In a preferred embodiment, the porous polymer membrane of the present invention is symmetrical. That is, when the porous polymer membrane is divided into a top portion, a body portion, and a bottom portion, each having the same thickness, along the thickness direction from the first main surface to the second main surface, the average pore size of each of the top portion, the body portion, and the bottom portion is not substantially different. In particular, the difference between the average pore size of each portion and the arithmetic mean of the average pore sizes of the top portion, the body portion, and the bottom portion is preferably no more than ±15%, more preferably no more than ±10%, and most preferably no more than ±5%. A typical configuration of the symmetrical membrane of the present invention is shown in... Figure 1 In this context, the supporting structure is contained within the membrane. As can be seen, the overall structure and properties of the membrane bridges on the two main surfaces of the membrane are very similar. Providing a symmetrical membrane ensures that the binding properties of this membrane are consistent throughout the membrane, i.e., there is no significant change in binding performance across the entire membrane, resulting in a uniformly distributed bound material during binding and elution chromatographic applications.

[0037] Regarding membrane bridges within porous polymer membranes, the ratio of the average bridge length to the average bridge width is preferably 5:1 to 7:1, and more preferably 5.5:1 to 6.5:1, if measured using a scanning electron microscope (SEM), at least 30 membrane bridges are measured and the average value is calculated.

[0038] Furthermore, the ratio of the average pore size to the average bridge width is preferably 2.0:1 to 4.0:1, more preferably 2.5:1 to 3.5:1, and most preferably 3.0:1 to 3.5:1. In this document, the average pore size can be determined as described above, and the average bridge width of the membrane bridge can be determined by analysis of CLSM micrographs.

[0039] According to a specific embodiment of the invention, the porous polymer membrane further includes a support structure, i.e., the support structure is part of the porous polymer membrane. If the porous polymer membrane of the invention includes a support structure as part of the membrane, all physical values ​​of the membrane described herein are determined using the membrane including the support structure. There are no particular limitations on the support structure, and therefore any support layer known to those skilled in the art can be used. For example, the support layer can be a nonwoven web, a woven fabric, or an open-cell microfiltration membrane. Examples of nonwoven webs are polyolefin nonwovens, such as PP / PE core-shell nonwovens and polyester nonwovens. The support layer is preferably a polyolefin nonwoven or a polyolefin membrane. Providing a support layer in the membrane described herein further improves the mechanical stability of the membrane while maintaining its excellent properties regarding the binding of substances, the flow rate of the mobile phase, and the internal surface area.

[0040] Preferably, the porous polymer membrane is a porous cellulose acetate membrane, a porous regenerated cellulose membrane, or a cross-linked cellulose membrane. That is, if the polymer is one of cellulose acetate, regenerated cellulose, or cross-linked cellulose, it is readily available in production and can be easily modified to carry chromatographic active centers useful in chromatographic analysis. In this document, cellulose acetate refers to a cellulose polymer that has been at least partially esterified with acetate. The term "regenerated cellulose membrane" refers to a cellulose membrane in which the cellulose structure is re-obtained from the esterification precursor through saponification. Furthermore, the term "cross-linked cellulose membrane" refers to a cellulose membrane that has been cross-linked at its hydroxyl groups.

[0041] When the porous polymer membrane is a porous cellulose acetate membrane, it preferably has an acetylation degree of 20% to 65%, more preferably 30% to 55%, even more preferably 35% to 50%, still more preferably 38% to 45%, and most preferably 40% to 42%. Within the above-mentioned range of acetylation degrees, the size of the membrane bridges is optimized to achieve a favorable convective porosity for improved chromatographic performance. The acetylation degree can be determined by near-infrared (NIR) spectroscopy. In NIR spectroscopy, the dried cellulose acetate material to be measured is irradiated with electromagnetic radiation in the near-infrared spectral range (i.e., with wavelengths of 800 to 2500 nm), and the absorption is measured. The obtained spectrum is compared with a series of spectra measured using the software Opus (Bruker) for a sample of cellulose acetate with a known acetyl content specified by the supplier. Here, the known acetyl content of the control sample is within the estimated acetylation degree of the cellulose acetate to be measured.

[0042] When the porous polymer membrane is a porous regenerated cellulose membrane, it preferably has a saponification degree of at least 50%, more preferably at least 70%, even more preferably at least 90%, still more preferably at least 95%, and most preferably 100%. A saponification degree within the above range results in a membrane that is sufficiently hydrophilic to, for example, avoid non-specific binding of hydrophobic contaminants. Furthermore, the membrane exhibits enhanced wettability, which is desirable for applications in chromatographic methods involving biomolecules. In this document, the degree of saponification is determined by measuring the weight loss during saponification and referencing a sample before saponification; therefore, the average degree of acetylation is assumed to be as shown in Table 1 below.

[0043] Table 1. Assumed degree of acetylation for the CDA / CTA ratio (cellulose diacetate / cellulose triacetate ratio) of the samples before saponification.

[0044] Furthermore, in a preferred embodiment, the porous polymer membrane is a saponified and crosslinked porous cellulose acetate membrane. As used herein, the term "saponified and crosslinked porous cellulose acetate membrane" refers to a cellulose acetate membrane that has been at least partially saponified and crosslinked. Specifically, the cellulose acetate membrane may be saponified and subsequently crosslinked at its newly formed hydroxyl groups. The cellulose acetate membrane may also be saponified and crosslinked simultaneously. The saponification and crosslinking processes are described, for example, in WO2007 / 017085 A2. By providing saponified and crosslinked membranes, high mechanical stability of the individual membranes is achieved. Therefore, for example, during drying, swelling and shrinkage upon contact with water (i.e., volume changes due to hydration) are minimized.

[0045] For the above crosslinking, a crosslinking agent is added to the membrane. The crosslinking agent has at least two functional portions that react with, for example, hydroxyl groups present in cellulose or regenerated cellulose. There are no limitations on the crosslinking agent, and it can be selected by those skilled in the art from known crosslinking agents. Preferably, the crosslinking agent is selected from diepoxides, diisocyanates, epichlorohydrin, epibromopropane, dimethylurea, dimethylvinylurea (1,3-dimethyl-2-imidazolium ketone), dichlorosilane, bis(2-hydroxyethyl) sulfone, divinyl sulfone, alkylene dihalides, hydroxyalkylene dihalides, glycidyl ethers, and combinations thereof.

[0046] In addition to the above, saponified and cross-linked porous cellulose acetate membranes can be modified with chromatographic active centers, i.e., saponified and cross-linked porous cellulose acetate membranes have chromatographic active centers attached to their saponified portions. In the case of porous polymer membranes that are regenerated cellulose membranes or saponified and cross-linked cellulose acetate membranes, the chromatographic active centers are preferably bound to the hydroxyl groups of cellulose. In this document, the term "chromatographic active center" (also referred to as "ligand") refers to a portion bound to the polymer material that is capable of interacting with and / or binding to components of the solution / mobile phase.

[0047] Regarding ligands / chromatographic active sites that interact with components of the mobile phase, examples that may be mentioned include, for instance, ion exchangers, chelating agents and heavy metal chelates, thiophilic and hydrophobic ligands of various chain lengths and configurations, reversed-phase systems, dye ligands, affinity ligands, amino acids, coenzymes, cofactors and their analogs, substrates and their analogs, endocrine and exocrine substances (e.g., active ingredients of hormones and hormone-like substances), effectors and their analogs, enzyme substrates, enzyme inhibitors and their analogs, fatty acids, fatty acid derivatives, conjugated fatty acids and their analogs, nucleic acids (e.g., DNA, RNA and their analogs and derivatives (single-stranded, double-stranded and / or multi-stranded)), and peptide nucleic acids and their derivatives, viruses, etc. Viral particles, monomers and their analogues and derivatives, oligomers to polymers and their analogues and derivatives, high molecular weight hydrocarbons (which may be linear or branched, unsubstituted or substituted), polymerized glycoconjugates (e.g., heparin, amylose, chitin, chitosan, and their monomers, oligomers, and their derivatives and analogues), lignin and its derivatives and analogues, other biochemical ligands, such as oligopeptides and polypeptides, such as proteins and their oligomers, polymers, subunits and their portions, especially lectins, antibodies, fusion proteins, haptens, enzymes and their subunits and their portions, structural proteins, receptors and effectors and their portions, as well as exogenous substances, drugs and active pharmaceutical ingredients, alkaloids, antibiotics, biomimetic substances, etc. Furthermore, the aforementioned ligands / chromatographic active sites, especially ion exchangers, chelating agents and heavy metal chelates, thiophilic and hydrophobic ligands of various chain lengths and configurations, and reversed-phase systems, can also be combined for mixed-mode chromatography.

[0048] Preferred examples of chromatographic active centers are ion exchangers, such as anionic and cationic groups, like sulfonic acid, phosphoric acid, or carboxylic acid groups, and quaternary ammonium groups. These ion exchanger chromatographic active centers are also used in combination in mixed-mode chromatography. The introduction of anionic ligands causes the modified porous polymer membranes to bind the cationic components of the solution while allowing the passage of anionic substances. Conversely, the introduction of cationic ligands causes the modified porous polymer membranes to bind the anionic components of the solution while allowing the passage of anionic substances.

[0049] According to the present invention, the use of the above-mentioned porous polymer membrane as an adsorption membrane is further provided, particularly as an adsorption membrane for the chromatographic separation of particles with a size of 1 to 500 nm, preferably 10 to 350 nm, more preferably 25 to 250 nm.

[0050] According to the present invention, a method for manufacturing the above-mentioned porous polymer membrane is further provided, comprising the steps of: a) Provide a polymer solution comprising at least one polymer, at least one first solvent, and at least one second solvent. b) Applying a polymer solution to the surface of a support to form a polymer layer on the support, and c) Evaporating at least one first solvent and at least one second solvent of a polymer solution to obtain a porous polymer membrane on a support; The polymer is a polysaccharide, and In step b), the polymer solution is applied at a thickness of 1000 to 2300 µm.

[0051] The features and (preferred) embodiments described above in the context of the porous polymer membrane of the present invention also apply to the method of manufacturing the porous polymer membrane of the present invention.

[0052] In principle, phase separation occurs in the above method. Specifically, at least one polymer is soluble in a polymer solution further comprising at least one first solvent and at least one second solvent, and said solution is applied to the surface of a support. Subsequently, as described below, at least one first solvent and at least one second solvent in the polymer solution are evaporated, and at least one polymer becomes insoluble in the modified solvent mixture. This results in the formation of a polymer-rich phase and a polymer-reduced phase. Due to continued evaporation, the polymer-rich phase solidifies, while the polymer-reduced phase further evaporates, yielding a porous polymer membrane. The characteristics of the specific steps will be further described below.

[0053] According to the present invention, in step a), a polymer solution is provided, the polymer solution comprising at least one polymer, at least one first solvent, and at least one second solvent. Any known method for providing the respective polymer solution may be applied.

[0054] In the method of the present invention, a combination of solvents in the polymer solution of step a) is used, namely at least one first solvent and at least one second solvent. Hereinafter, the at least one first solvent is preferably volatile, while the at least one second solvent is preferably a so-called "non-solvent," i.e., a liquid that cannot dissolve at least one polymer forming a film. Furthermore, at least the first solvent and at least the second solvent are not the same; that is, at least one first solvent and at least one second solvent are different from each other.

[0055] There are no particular limitations on at least one first solvent, except that it is preferably volatile. In this case, the term "volatile" means that the respective substance preferably has a boiling point temperature (bp) below 100°C at 1013 hPa (boiling point) and a vapor pressure (vp) of at least 200 hPa at 20°C. Examples of at least one first solvent are acetone (bp 56 ℃, vp 246 hPa), tetrahydrofuran (bp 65 ℃, vp 170 hPa), methyl acetate (bp 57 ℃, vp 228 hPa), methyl ethyl ketone (bp 80 ℃, vp 105 hPa), methyl formate (bp 32 ℃, vp 638 hPa), ethyl formate (bp 54 ℃, vp 266 hPa), and dichloromethane (bp 40 ℃, vp 470 hPa). The boiling point (bp) at 1013 hPa and the vapor pressure (vp) at 20°C are given in parentheses. Preferably, at least one first solvent is selected from acetone, methyl acetate, methyl formate, ethyl formate, and dichloromethane; more preferably, at least one first solvent is selected from acetone and dichloromethane. The solvents can be used alone or in any combination. Preferably, one or two first solvents are used. The use of volatile first solvents (e.g., acetone, methyl acetate, methyl formate, ethyl formate, and dichloromethane) is advantageous because their low viscosity results in a lower viscosity of the casting solution / polymer solution, which provides improved processability compared to casting solutions with higher viscosity (and the same amount of solids).

[0056] The polymer solution further comprises at least one second solvent for the selected polymer, said solvent preferably being a non-solvent. As previously stated, in this document, the term "non-solvent" refers to a liquid that cannot dissolve at least one of the film-forming polymers. The at least one second solvent for at least one film-forming polymer (i.e., each of the film-forming polymers in the case of more than one polymer) preferably has a solubility of at most 1% by weight, more preferably at most 0.1% by weight, under standard conditions (in each case).

[0057] The maximum concentration of at least one second solvent (or precipitant) is insufficient to cause precipitation of at least one film-forming polymer. The polymer solution may consist solely of at least one first solvent, at least one corresponding film-forming polymer, and at least one second solvent. Alternatively, the polymer solution may consist of one first solvent, one or two film-forming polymers, and two second solvents.

[0058] Suitable second solvents include, for example, water, glycerol, methanol, ethanol, n-propanol, and isopropanol, as well as mixtures thereof. Preferably, at least one second solvent is water and / or ethanol, and more preferably, ethanol.

[0059] Compared to conventional methods, this approach preferably requires no additional machinery or equipment. Preferably, it uses non-toxic reagents or other substances of high concern. The process design described herein further reduces production costs and simplifies the control of key process parameters.

[0060] Relative to the total mass of the polymer solution, the polymer solution may contain 2.0 wt% to 15 wt% of at least one (film-forming) polymer, 30 wt% to 75 wt% of at least one first solvent, and 0.1 wt% to 55 wt% of at least one second solvent. The content of at least one (film-forming) polymer is more preferably 3.0 wt% to 8.0 wt% and most preferably 5.0 wt% to 7.0 wt%. The content of at least one first solvent relative to the total mass of the polymer solution is preferably 35 wt% to 70 wt%, more preferably 40 wt% to 65 wt%. The content of at least one second solvent relative to the total mass of the polymer solution is preferably 25 wt% to 50 wt%, more preferably 30 wt% to 40 wt%. When the polymer solution contains more than one (film-forming) polymer, first solvent, and / or second solvent, the above amounts refer to the sum of the respective components. By providing a polymer solution with a composition within the above range, a porous polymer membrane with an optimal balance between convective porosity, thickness, and average pore size can be manufactured, while also being highly symmetrical.

[0061] The polymer solution may further contain one or more additives to improve industrial applicability on a large scale. Suitable additives are, for example, swelling agents, solubilizers, hydrophilic agents, and / or pore-forming agents (spherical pore-forming agents). The respective additives are known to those skilled in the art and are suitable for the film-forming polymer. For example, glycerol, triacetin, Tween 20, Tween 80, or citric acid may be used additives. Such additives are included in the polymer solution in an amount of 0 wt% to 10 wt%. Preferably, such additives are included in the polymer solution in a total amount of 5 wt% or less, more preferably 3 wt% or less, and most preferably 1 wt% or less. The polymer solution may consist of at least one corresponding film-forming polymer, at least one first solvent, at least one second solvent, and optionally one or more additives, preferably pore-forming agents and / or swelling agents.

[0062] The polymer solution does not require any specific thermal pretreatment; that is, the thermal pretreatment used for film / structure formation is unnecessary. More specifically, the polymer solution preferably does not have any lower critical solution temperature to avoid segregation of the polymer solution prior to evaporation in subsequent steps.

[0063] In a preferred embodiment, the polymer solution comprises cellulose diacetate (CDA) and optionally cellulose triacetate (CTA) as polymers to obtain a porous polymer membrane, which is a porous cellulose acetate membrane. That is, the polymer solution may contain CDA as the membrane-forming polymer only, or the polymer solution may contain both CDA and CTA as membrane-forming polymers. There are no limitations; the polymer solution may, for example, contain CDA as the membrane-forming polymer only, if acetone is also contained as a volatile solvent. Furthermore, the polymer solution may, for example, contain both CDA and CTA as membrane-forming polymers, if dichloromethane is also contained as a volatile solvent. By applying CDA and optionally CTA, the resulting membrane comprises a large number of membrane bridges, which have a small average bridge width and a narrow distribution of bridge width and length. Therefore, the convective porosity of the resulting membrane can be increased.

[0064] When using a mixture of CDA and CTA, depending on both at least one first solvent and at least one second solvent, the polymer solution preferably contains 50 wt% to 70 wt% CDA and 30 wt% to 50 wt% CTA relative to the total polymer content in the polymer solution. More preferably, the polymer solution contains 55 wt% to 65 wt% CDA and 35 wt% to 45 wt% CTA. Most preferably, the ratio of CDA to CTA in the polymer solution is 65 wt%:35 wt% to 60 wt%:40 wt% relative to the total polymer content in the polymer solution. In particular, the contents of CDA and CTA, as well as the CDA to CTA ratio, can affect the formation of membrane bridges; a high CTA content generally results in wide membrane bridges (i.e., membrane bridges with high width), while a high CDA content results in lower membrane bridge volume (i.e., membrane bridges with low width). These parameters have a significant impact on the convective porosity of the membrane.

[0065] According to the invention, in step b), the polymer solution is applied to the surface of the carrier to form a polymer layer on the carrier. Methods for applying the polymer solution are known in the art and can be used without particular limitation in the method of the invention. These methods include, for example, methods of transferring the carrier, where the corresponding polymer solution emerges from a conventional scraping system or slit mold. Step b) preferably occurs using a slit mold.

[0066] In step b), the polymer solution is applied with a thickness of 1000 to 2300 μm, preferably 1100 to 2000 μm, and more preferably 1200 to 1500 μm. Applying the polymer solution to this thickness yields a film with a thickness of 150 to 1000 μm. It should be noted that those skilled in the art can adjust the thickness of the polymer layer according to the concentration of at least one polymer forming the film in the polymer solution.

[0067] When the membrane includes a support structure, the support structure can be provided on the polymer layer after the application of the polymer solution. In this way, the polymer solution can partially or completely permeate into the optional support structure and replace the air contained in the support structure. For example, the polymer layer can permeate into the support structure to a degree of at least 25%, preferably at least 50%, more preferably at least 75%, and most preferably up to about 100% (i.e., completely). To obtain a highly symmetrical membrane, the permeation depth into the support structure should be within the above-mentioned range.

[0068] The thickness of the support structure can be, for example, 15 to 500 µm, preferably 35 to 300 µm, and more preferably 50 to 200 µm.

[0069] Any carrier suitable for membrane production methods from the prior art can be used. The carrier preferably has a flat surface and is inert relative to the substance used (e.g., polymer solutions and their components). A moving belt (conveyor belt) or roller is preferably used as the carrier, each preferably made of steel or plastic foil, thereby enabling the continuous implementation of the method.

[0070] Basic preparation methods known in the art are described, for example, in WO 2023 / 088888 A1 and EP 4 180 117 A1.

[0071] The application temperature in step b) can be from 4°C to (the (lowest boiling point) of the volatile solvent in °C – 20% (relative to the (lowest boiling point) of the volatile solvent)), more preferably from 4°C to (the (lowest boiling point) of the volatile solvent – ​​25%), and most preferably from 4°C to (the (lowest boiling point) of the volatile solvent – ​​30%). For example, if the boiling point of the volatile solvent (lowest boiling point) is 100°C, the range of 4°C to (the (lowest boiling point) of the volatile solvent – ​​20%) means 4°C to (100°C – 20°C) = 4°C to 80°C. Preferably, the temperature in step b) is from 4°C to 30°C, more preferably from 10°C to 20°C. Applying the above temperature range enables the controlled application of the polymer solution to the carrier, including optimized viscosity of the polymer solution.

[0072] Preferably, the method of the present invention includes only one polymer solution application step, and therefore there are no further polymer solution application steps other than step b).

[0073] According to the invention, in step c), at least one first solvent and at least one second solvent of the polymer solution are evaporated to obtain a porous polymer membrane on a carrier. This is, for example, carried out by transporting the polymer layer from step b) through an evaporation zone for partial evaporation of at least one first solvent and at least one second solvent, preferably at a relative humidity of less than 20% RH. Due to the high thickness of the polymer layer, the evaporation step should preferably meet the following specific requirements.

[0074] The evaporation time in step c) is preferably 10 to 45 minutes, more preferably 12 to 35 minutes, and most preferably 15 to 30 minutes. When such an evaporation time is applied, sufficient evaporation of at least one volatile solvent from the polymer layer having the above-mentioned thickness is achieved by ensuring that the at least one volatile solvent effectively diffuses through the polymer layer to the exposed surface of the layer opposite the carrier.

[0075] The temperature in step c) can be the same as, higher than, or lower than the temperature in step b). This temperature preferably allows for the prevention of bubble formation in the film layer, which can lead to significant defects. When such a temperature is applied, sufficient evaporation of at least one volatile solvent can be achieved. Specifically, using the same temperature as in step b) ensures that at least one volatile solvent effectively diffuses through the polymer layer, and a symmetrical film can be achieved.

[0076] The evaporation zone allows for control of the humidity, temperature, and optional airflow conditions of the atmosphere. Specifically, at the temperature used in step c), the humidity of the evaporation zone relative to the ambient environment is preferably reduced to below 20% RH, more preferably below 18% RH, even more preferably below 15% RH, even more preferably below 10% RH, and most preferably 0% to 5% RH. This typically allows for the avoidance of deteriorating effects due to water diffusion into the membrane (i.e., the openings in the membrane at the top portion). The required relative humidity (RH) can be regulated, for example, by introducing a dry gas, preferably an inert gas such as nitrogen or carbon dioxide, into the evaporation zone.

[0077] Furthermore, the gas flow velocity above the polymer layer is 0.01 to 1.0 m / s, preferably 0.1 to 0.5 m / s. Using this velocity, even at temperatures below the boiling point of the at least one volatile solvent, the at least one volatile solvent can evaporate uniformly and sufficiently, while ensuring effective diffusion of the at least one volatile solvent through the polymer layer and the fabrication of a symmetrical film.

[0078] Preferably, the above method further includes step d) of saponifying and crosslinking the porous cellulose acetate membrane to obtain a saponified and crosslinked porous cellulose acetate membrane. Regarding the saponification and crosslinking steps, all the details above concerning the saponified and crosslinked membrane apply to the methods described herein.

[0079] The method for manufacturing a porous polymer membrane may further include step e) of modifying a saponified and crosslinked porous cellulose acetate membrane. For the modification step, refer to the description above regarding modified porous polymer membranes.

[0080] By providing the aforementioned porous polymer membrane and the method for manufacturing the porous polymer membrane described above, a high binding capacity of the membrane is achieved in chromatographic applications, while maintaining a high flow rate of fluid through or across the membrane. Therefore, the porous polymer membrane described herein is well-suited for applications such as binding and elution chromatography.

[0081] The attached diagram shows: Figure 1 Scanning electron micrographs of the two main surfaces and cross-sections of the symmetrical film according to the invention are shown.

[0082] Figure 2a ) The diagram shows a comparison of the relationship between the binding capacity of negatively charged latex particles and membrane permeability in conventional and the present invention Q-membranes, according to Example 3.

[0083] Figure 2b ) The diagram shows a comparison of the permeability versus internal surface area of ​​conventional and the present invention Q-membranes according to Example 3.

[0084] Figure 3 The diagram shows the relationship between the binding capacity of the membrane of the present invention, modified with a primary amine ligand, and the flow rate, according to Example 4, compared to a conventional membrane.

[0085] Figure 4 The diagram shows the relationship between the BSA binding capacity and flow rate of the membrane of the present invention modified with phenyl ligands, according to Example 4, compared to a conventional membrane.

[0086] The invention will be further illustrated in the following examples, but is not limited thereto.

[0087] Example

[0088] Material

[0089] Commercially available cellulose diacetate (CDA) (Mn = 60,000 to 150,000 g / mol) has a degree of acetylation of 38.0% to 40.5%.

[0090] Commercially available cellulose triacetate (CTA) (Mn = 100,000 to 200,000 g / mol) has a degree of acetylation of 43.0% to 44.5%.

[0091] Example 1: Membrane Preparation

[0092] First, at ambient temperature, polymer solutions of cellulose diacetate and (optionally) cellulose triacetate were prepared using dichloromethane or acetone as volatile solvents and ethanol and / or water as non-solvents, according to the compositions shown in Table 2. Subsequently, the airflow velocity above the polymer layer was reduced to 0.2 m / min, and the polymer solution was applied to a stainless steel solid substrate at 10°C with a thickness of 1400 µm for 25 minutes. In the case of membranes 1 and 4, polyester fleece, having a thickness of 200 to 260 µm and a surface area per unit weight of 26 to 40 g / m², was applied to the polymer layer as a support structure, while membranes 2 and 3 were processed without a support structure. Subsequently, the respective volatile solvents were evaporated at 20°C for 15 to 45 minutes (until the polymer layer exhibited a white appearance), with an airflow velocity of 0.5 m / s above the polymer layer.

[0093] Table 2. Composition of the polymer solution (all values ​​are given in wt%) and properties of the obtained membranes

[0094] Each of membranes 1 to 4 has an average pore size of 0.45 µm to 10.0 µm, a thickness of 150 to 1000 µm, a convective porosity of at least 65% (or even at least 80%), and satisfies relation (1).

[0095] Example 2: Symmetrical membrane

[0096] The membrane according to the present invention was prepared as described in Example 1. As described above, the symmetry of the membrane was analyzed by dividing the membrane along the thickness direction from the first main surface to the second main surface into a top portion, a main portion, and a bottom portion having the same thickness. The CLSM of the entire membrane was measured, and the obtained microscopic images were divided according to the aforementioned partitions. The respective average pore size and average bridge width derived therefrom are shown in Table 3 below, together with the values ​​obtained from Comparative Product 5 and Comparative Product 6 of Example 3 below.

[0097] Table 3. Average pore size and average bridge width of membranes 5 and 6, and comparative products 5 and 6, and their ratios (see Example 3 below).

[0098] As can be seen from Table 3 above, there is no substantial difference in the average pore size of each of the top, main, and bottom portions of membranes 5 and 6. Specifically, the difference between the average pore size of each portion and the average value is very low, indicating that the membrane described in this invention exhibits high symmetry.

[0099] Example 3: Modification of membrane surface with quaternary ammonium groups

[0100] To produce a membrane suitable for chromatography and modified with cationic ligands / chromatographic active sites, the cellulose acetate membrane according to the invention (having an average pore size of 0.45 to 10.0 μm, a thickness of 150 to 1000 μm, and a convective porosity of at least 65% (even at least 80%), and satisfying relation (1)) is first saponified and crosslinked for 19 hours using 15% 1,4-butanediol diglycidyl ether and 0.6% NaOH aqueous solution to obtain a crosslinked regenerated cellulose membrane. Subsequently, the crosslinked regenerated cellulose membrane is functionalized / modified by applying 10% trimethylamine aqueous solution to obtain a Q membrane, i.e., a cationic membrane carrying quaternary ammonium sites.

[0101] To evaluate the chromatographic suitability of Q membranes for binding negatively charged model particles (latex particles, micromers) with a diameter of 100 nm, binding capacity was measured and compared with commercially available Q membranes (Sartorius Sartobind Q, Millipore Natrix-Q, Pall Mustang-Q, and BIA CIMmultus QA). The relationship between the binding capacity and permeability of the membranes is as follows: Figure 2a As shown in the figure, and the relationship between permeability and a specific internal surface area is as follows: Figure 2b As shown in the figure.

[0102] Binding capacity was determined using 100 nm PS latex particles: The membrane sample (a circular disk with d = 6 mm) was placed in a sample holder and rinsed with Tris-buffered saline (pH = 7) using a Knauer filtration device. After rinsing, the sample was passed through a model particle suspension (100 nm latex particles) at a constant flow rate. The breakthrough curve was determined by the UV absorption signal of the solution at 200 nm, and the dynamic binding capacity (i.e., the number of particles per unit membrane volume) was calculated from the volume of the filtered particle solution at 10% breakthrough, thus taking into account the particle concentration (approximately 10¹). 0 (particles / ml).

[0103] In this article, reference Figure 2a The relationship between capacity and a specific inner surface is as follows:

[0104] Among them, A i Let BC be the specific inner surface area in m² / mL membrane volume, and BC be the binding capacity in 100 nm particle number × 10¹² / mL membrane volume. Using the above formula, the specific inner surface area can be calculated based on the binding capacity, serving as an alternative to the known BET method.

[0105] Comparative Product 1: Sartorius Sartobind Q, a cross-linked regenerated cellulose membrane modified with quaternary ammonium groups, thickness: 270 µm, convective porosity: 75%, nominal pore size: 5 µm, permeability: 99 mD, internal surface area: 2.3 m² / g. Comparative Product 1 does not satisfy relation (1).

[0106] Comparison Product 2: Millipore Natrix-Q, a veloured fabric with porous polyacrylamide hydrogel, thickness: 500 µm, nominal pore size: 0.4 µm, permeability: 0.3 mD. Comparison Product 2 is a polysaccharide-free membrane.

[0107] Comparative Product 3: Pall Mustang-Q, a hydrophilic modified polyethersulfone membrane, with a monolayer thickness of 175 µm, a nominal pore size of 0.8 µm, and a permeability of 10 mD. Comparative Product 3 is a polysaccharide-free membrane.

[0108] Comparison Product 4: BIA CIMmultus QA, a monolithic poly(glycidyl methacrylate-copolymer-ethylene glycol dimethacrylate) material, thickness: 6550 µm, nominal pore size 1.3–6.0 µm, permeability (nominal pore size 1.3 µm): 0.5 mD, inner surface area (1.3 µm): 7.7 m² / g; permeability (nominal pore size 2.0 µm): 8 mD, inner surface area (2.0 µm): 5.5 m² / g; permeability (nominal pore size 6.0 µm): 15 mD, inner surface area (6.0 µm): 2.2 m² / g. Comparison Product 4 is a polysaccharide-free membrane.

[0109] Comparative Product 5: Sartorius quaternary ammonium group modified crosslinked regenerated cellulose membrane, thickness: 270 µm, convective porosity: 75%, nominal pore size: 5 µm, permeability: 200 mD, internal surface area: 1.2 m² / g. Comparative Product 5 does not satisfy relation (1).

[0110] Comparative Product 6: Cytiva ST69, a cross-linked regenerated cellulose membrane modified with quaternary ammonium groups, thickness: 124 µm, convective porosity: 85%, nominal pore size: 1.2 µm, permeability: 15 mD, internal surface area: 5.2 m² / g. Comparative Product 5 does not have a thickness of at least 150 µm and does not satisfy relation (1).

[0111] The membrane of the present invention is a crosslinked regenerated cellulose membrane modified with quaternary ammonium groups according to the membrane 2 of Example 1, having an average pore size of 0.45 to 10.0 µm, a thickness of 150 to 1000 µm, a convective porosity of at least 65% (or even at least 80%), and satisfying relation (1).

[0112] As can be seen, when compared to commercially available Q-membranes, the membrane according to the invention exhibits increased binding capacity at similar permeabilities, or higher permeability at a given binding capacity (see [link to relevant documentation]). Figure 2b Furthermore, compared to commercially available Q-membranes, the membrane according to the present invention exhibits optimized permeability and a specific internal surface area (see [link]). Figure 2b ).

[0113] Example 4: Chromatographic membrane with a "dual-pore" structure

[0114] The cellulose acetate membrane according to the invention (having an average pore size of 0.45 to 10.0 µm, a thickness of 150 to 1000 µm, and a convective porosity of at least 65% (even at least 80%), and satisfying relation (1)) is fully saponified under swelling conditions and subsequently crosslinked as described in DE 10 2008 018732 B4. Due to saponification under swelling conditions, the membrane bridges of the membrane become more porous, creating additional binding sites for small molecules such as antibodies.

[0115] Comparative membranes 7 and 8: Sartorius Sartobind STIC PA / Pheny, amine- or phenyl-modified cellulose acetate membranes, thickness: 270 to 330 µm, convective porosity: 75%, nominal pore size: 1 to 2 µm, permeability: 20 to 25 mD, specific internal surface area: 3.5 to 4.0 m² / g. Comparative membranes 7 and 8 do not satisfy relation (1).

[0116] The membrane of the present invention is an amine or phenyl modified cellulose acetate membrane having an average pore size of 0.45 to 10.0 µm, a thickness of 150 to 1000 µm, and a convective porosity of at least 65%, and satisfying the relation (1).

[0117] The prepared membranes were further modified using primary amine ligands or phenyl ligands as chromatographic active sites. Subsequently, the binding capacity of bovine serum albumin (BSA) in the amino-modified cellulose acetate membrane and the binding capacity of γ-globulin in the phenyl-modified cellulose acetate membrane were measured in relation to the flow rate of the mobile phase passing through the membrane, as shown below. Figure 3 and Figure 4 As shown. In this document, the references shown in the figures are commercially available Sartorius Sartobind Phenyl membranes or Sartorius Sartobind STIC PA membranes, which have been similarly modified.

[0118] like Figure 3 and Figure 4 As can be seen, compared with commercially available membranes (Comparative Membrane 7 and Comparative Membrane 8), the two modified membranes of the present invention achieve higher binding capacity of BSA (amine-modified) or γ-globulin (phenyl-modified) at a given flow rate, or at a higher flow rate for a given binding capacity.

Claims

1. A porous polymer membrane having a first main surface, a second main surface, and membrane bridges, wherein the membrane bridges are solid polymer bulk materials surrounding and defining the pores of the membrane. The polymer is a polysaccharide. The average pore size of the membrane pores in the porous polymer membrane is between 0.45 µm and 10.0 µm. The porous polymer membrane has a thickness of 150 µm to 1000 µm. The convective porosity of the porous polymer membrane is at least 65%, and The porous polymer membrane exhibits a permeability (P) and a specific internal surface area (A) as defined by the following equation (1). i The relationship between ) Where P is the permeability in mD, and A i For m 2 The specific internal surface area relative to the weight of the porous polymer membrane, in units of g, is A at least 835 mD, B at least 1.10 g / m², and C at least 14 mD.

2. The porous polymer membrane according to claim 1, wherein the porous polymer membrane is a porous cellulose acetate membrane, a porous regenerated cellulose membrane, or a cross-linked cellulose membrane.

3. The porous polymer membrane according to claim 2, wherein the porous polymer membrane is a porous cellulose acetate membrane having an acetylation degree of 30% to 55%.

4. The porous polymer membrane according to any one of claims 1 to 3, wherein the porous polymer membrane has a permeability of 20 mD to 5000 mD.

5. The porous polymer membrane according to any one of claims 1 to 4, wherein the ratio of the average pore size of the porous polymer membrane to the average bridge width of the porous polymer membrane is 2.0:1 to 4.0:

1.

6. The porous polymer membrane according to any one of claims 1 to 5, wherein the ratio of the average bridge length of the membrane bridge to the average bridge width of the membrane bridge is 5:1 to 7:

1.

7. The porous polymer membrane according to any one of claims 1 to 6, wherein when the porous polymer membrane is divided in the thickness direction from the first main surface to the second main surface into a top portion, a body portion and a bottom portion each having the same thickness, the average pore size of each of the top portion, the body portion and the bottom portion is not substantially different.

8. The porous polymer membrane according to any one of claims 1 to 7, wherein the convective porosity of the porous polymer membrane is at least 80%.

9. The porous polymer membrane according to any one of claims 1 to 8 further comprises a support structure.

10. The porous polymer membrane according to any one of claims 1 to 9, wherein the porous polymer membrane is a saponified and cross-linked porous cellulose acetate membrane, wherein the saponified and cross-linked porous cellulose acetate membrane preferably has chromatographic active centers connected to its saponified portion.

11. Use of the porous polymer membrane according to any one of claims 1 to 10 as an adsorption membrane.

12. A method for manufacturing a porous polymer membrane according to any one of claims 1 to 9, comprising the following steps: a) Provide a polymer solution comprising at least one polymer, at least one first solvent, and at least one second solvent. b) Applying the polymer solution to the surface of the carrier to form a polymer layer on the carrier, and c) Evaporating the polymer solution of at least one first solvent and at least one second solvent to obtain a porous polymer membrane on the support; The polymer is a polysaccharide, and The polymer solution described in step b) is applied with a thickness of 1000 µm to 2300 µm.

13. The method of claim 12, wherein the evaporation of the at least one first solvent and the at least one second solvent of the polymer solution in step c) lasts for a duration of 15 minutes to 45 minutes.

14. The method according to claim 12 or 13, wherein the polymer solution comprises cellulose diacetate and optionally cellulose triacetate to obtain a porous polymer membrane, said porous polymer membrane being a porous cellulose acetate membrane.

15. The method of claim 14, further comprising step d) of saponifying and crosslinking the porous cellulose acetate membrane to obtain a saponified and crosslinked porous cellulose acetate membrane.

Citation Information

Patent Citations

  • Method for substance separation using a cellulose hydrate membrane in size exclusion chromatography

    DE102008018732B4

  • Membrane for microbiological analysis

    EP4180117A1

  • Process for cross-linking cellulose ester membranes

    WO2007017085A2

  • Cellulose hydrate membrane, method for the production thereof, and use thereof

    WO2009127285A1

  • Membrane for microbiological analysis

    WO2023088888A1